PROPOSED CORPORATE STRATEGY AND ITS IMPLICATION FOR PT GARUDA INDONESIA - Prabowo, Firman
The presence of the Covid-19 pandemic has not only had an effect on health on a global scale but has also had an effect on the industry of the entire community. It was one of the most difficult times for the aviation industry because the aviation industry was one of the industries that was hit the hardest. This caused it to be one of the darkest times in the aviation industry. The national airline of Indonesia, Garuda Indonesia, was significantly impacted as a result of this. It wasn't long before Garuda Indonesia ran into financial trouble; roughly two years after the COVID-19 pandemic, the airline was facing the possibility of going bankrupt due to their mounting debt. In a general sense, businesses that are in possession of an advantage have a better chance of surviving challenging conditions and the pressures of competitive pressures in an industry. Because of this, Garuda Indonesia needs to assess their position in the industry, conduct an audit of the company's internal and external conditions, and figure out how to make the most of their competitive advantage.